Pengaruh Minat Belajar Yang Dikontrol Oleh Waktu Belajar Terhadap Keaktifan Belajar Siswa SMA Negeri 1 Rengat - Fadhillah, Arifah; Prabowo, Andri Eko; Marliati, Lina (UIR Press, 2024)
This study aims to analyze 1) the influence of learning interest on learning activity, 2) the influence of learning interest controlled by learning time on learning activity. This study uses a quantitative descriptive approach with a comparative method. Data collection was carried out through a questionnaire distributed to 84 students of class XII IPS SMA Negeri 1 Rengat using the proprotional random sampling technique using the slovin formula. The data analysis uses descriptive techniques, classical assumption tests, and hypothesis tests. The results of this study show that: 1) learning interest has a significant influence on learning activity, 2) there is an influence of learning interest controlled by learning time on learning activity.